2014
DOI: 10.1016/j.celrep.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Origin-Dependent Neural Cell Identities in Differentiated Human iPSCs In Vitro and after Transplantation into the Mouse Brain

Abstract: The differentiation capability of induced pluripotent stem cells (iPSCs) toward certain cell types for disease modeling and drug screening assays might be influenced by their somatic cell of origin. Here, we have compared the neural induction of human iPSCs generated from fetal neural stem cells (fNSCs), dermal fibroblasts, or cord blood CD34(+) hematopoietic progenitor cells. Neural progenitor cells (NPCs) and neurons could be generated at similar efficiencies from all iPSCs. Transcriptomics analysis of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 21 publications
4
41
0
Order By: Relevance
“…S1d)8910. This approach revealed efficient neuronal differentiation in both groups and demonstrated that neuronal differentiation per se was not impaired in FTD NPCs, as similarly seen in a previous study on N279K MAPT mutant neurons10.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…S1d)8910. This approach revealed efficient neuronal differentiation in both groups and demonstrated that neuronal differentiation per se was not impaired in FTD NPCs, as similarly seen in a previous study on N279K MAPT mutant neurons10.…”
Section: Resultssupporting
confidence: 82%
“…Also, co-cultured neurons and astrocytes carried comparable regional profiles, consistent with the fact that both neural cell types had been derived from the same NPC population with similar regional programs (Fig. S4e)9. Altogether, these findings indicated that FTD astrocytes could render neighboring neurons more vulnerable to respiratory stress.…”
Section: Resultssupporting
confidence: 77%
“…The studies of cell-of-origin indicated that the parental cell could influence the differentiation capacity of the resultant iPS cells [33]. There were some reports that showed iPS cells derived from nonhematopoietic cells (neural progenitors and fibroblasts) retained residual methylation [3436]. Some evidences showed iPS cells retained a residual transcriptional memory of the somatic cells and provided data in support of inefficient promoter DNA methylation as the underlying mechanism [14, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, iPSCs derived from primary human fetal retinal pigmented epithelial (RPE) cells can retain memory of their previous differentiation state and exhibited a preference to redifferentiate into RPE (Hu et al, 2010). In some iPSC lines, this epigenetic memory is reduced with each passage in culture (Kim et al, 2010) but it is possible that some forms of epigenetic memory are more stable and can be exploited in selecting iPSC lines for stem cell based therapies (Hargus et al, 2014). To date, most studies of epigenetic memory in iPSCs have focused on DNA methylation but higher order chromatin organization mediated by insulator element such as CTCF may also play a role in iPSC epigenetic memory (Narendra et al, 2015).…”
Section: Introductionmentioning
confidence: 99%